United Nations and Gender Equality in Nigeria: A Reference of 2010-2020 - IJE O. JAIRUS; AJIYA SARAH; KARUEJE UCHE CHRISTOPER (International Studies Journal)
The study examines United Nations and Gender Equality in Nigeria a reference of 2010 to 2020. The study made use of secondary sources of data as veritable tools for its analysis. Survey research method was used. The study revealed that the menace of marginalization, deprivation, poverty, exploitation, discrimination, oppression and the violation of women's rights by men, institutions, religion and culture is still ongoing in Nigeria despite the main goal of the United Nations Organization (UNO) which is the protection and promotion of the fundamental human rights and the freedom of both men and women without discrimination on the basis of race, sex, language or religion. The gap of the study is that all gender violations in Nigeria should be outlawed. The study is anchored on Eager's Model of International Norm Construction Theory. The study concludes that despite many conventions, commissions and declarations established and declared by UN and her agencies, the status of women is still suppressed by men, religion, institutions and cultures in Nigeria. It finally recommends that women status can only be enhanced and can contribute meaningfully to the socio economic and political development of our society if all forms of gender biases are removed and women are not regarded as inferior beings but as people created with equal endowment by God.